PENYEBAB PERBAIKAN KEBOCORAN PIPA AIR BERSIH PADA JALAN RAYA KOTA SUNGAI PENUH - Ilvani, Maria; Carlo, Nasfryzal; Mizwar, Zuherna (Prosiding TAU SNARS-TEK Seminar Nasional Rekayasa dan Teknologi, 2025)
Water distribution pipe is one of the most basic infrastructure of any modern organization from small villages to cities. Based on data from Perumda Tirta Khayangan, Sungai Penuh City in 2022; The level of leaks and distribution pipe repair location in the last three years has increased by 34.56% with repairs of 963 location in 2020, 1,042 location in 2021 and 865 location in 2022.The location of repairment for water distribution pipe is mostly on roads and/or across roads, causing disruption to the road and even traffic due to seepage caused when leaks occur or when repairs are carried out.Therefore, this research was carried out to determine the factors that influence the repairment of leaked piping and leaked of clean water distribution pipe on the highways of Sungai Penuh City. The method used is quantitative descriptive by distributing questionnaires to respondents. The number of respondents was 35 people.The research results show five factors that influence distribution pipe repairment, such as pipe condition and environments, pipe specifications and human resources, operations and management, as well as technical documents and coordination. Based on these five factors, it was found that the most influential factors were pipe conditions and soil conditions.